2019
DOI: 10.1186/s12968-019-0536-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of cardiovascular magnetic resonance-derived circumferential strain parameters with the risk of ventricular arrhythmia and all-cause mortality in patients with prior myocardial infarction and primary prevention implantable cardioverter defibrillator

Abstract: Background Impaired left ventricular (LV) contraction and relaxation may further promote adverse remodeling and may increase the risk of ventricular arrhythmia (VA) in ischemic cardiomyopathy. We aimed to examine the association of cardiovascular magnetic resonance (CMR)-derived circumferential strain parameters for LV regional systolic function, LV diastolic function and mechanical dispersion with the risk of VA in patients with prior myocardial infarction and primary prevention implantable cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…For other factors, LVEF, percentage of BZ mass, percentage of IC mass, percentage of IBZ mass, IC entropy, IBZ entropy, and GLS were correlated with SCD and dangerous VA, similar to other post‐MI research 19 . Whereas GCS was not a statistical prognostic parameter in our study and different from Elisabeth's research 36 . The trial involved 121 post‐MI patients referred for primary prevention ICD implantation and found circumferential strain parameters were associated with appropriate ICD therapy, after adjusting for the effects of LVEF and BZ mass% 36 .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…For other factors, LVEF, percentage of BZ mass, percentage of IC mass, percentage of IBZ mass, IC entropy, IBZ entropy, and GLS were correlated with SCD and dangerous VA, similar to other post‐MI research 19 . Whereas GCS was not a statistical prognostic parameter in our study and different from Elisabeth's research 36 . The trial involved 121 post‐MI patients referred for primary prevention ICD implantation and found circumferential strain parameters were associated with appropriate ICD therapy, after adjusting for the effects of LVEF and BZ mass% 36 .…”
Section: Discussionsupporting
confidence: 80%
“…19 Whereas GCS was not a statistical prognostic parameter in our study and different from Elisabeth's research. 36 The trial involved 121 post-MI patients referred for primary prevention ICD implantation and found circumferential strain parameters were associated with appropriate ICD therapy, after adjusting for the effects of LVEF and BZ mass%. 36 Choosing different endpoint events, the inclusion of radial and longitudinal strain parameters can explain the inconsistency.…”
Section: Prognostic Importance Of Bz Entropy and Gls In Patients Afte...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mordi et al found GCS derived by harmonic phase myocardial tagging to be independently prognostic in their single-centre study of 539 unselected patients undergoing CMR after adjusting for LVEF and LGE [ 32 ]. Paiman et al found the extent of moderately impaired LV GCS to be associated with appropriate ICD therapy in 121 patients with primary prevention ICDs and history of previous myocardial infarction [ 33 ]. However, this original study was relatively small with only 30 events and, the endpoint of appropriate ICD therapy included ATP in addition to shocks.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, a simplified deformation analysis with high reproducibility is possible [41] and analyses even without dedicated post processing software are conceivable. Importantly, by predicting ventricular arrhythmia or early myocardial remodelling very accurately [42,43], CMR-FT-based LV strain was found to outperform traditionally used LVEF in these studies further questioning current approaches using a LVEF cut of 35% for defibrillator device therapy and raising considerations of new risk classifications beyond this parameter. Of note, not only global LV strain analyses but also regional CMR-derived strain evaluations of non-infarcted remote myocardium were shown to allow an extended risk classification and categorise new high-risk groups in patients suffering AMI [44].…”
Section: Deformation Analyses In Acute and Chronic Ischemiamentioning
confidence: 93%